Post-Translational Modifications of Proteins in Cytosolic Nucleic Acid Sensing Signaling Pathways - Deng, Yu; Wang, Ying; Li, Lupeng; Miao, Edward A.; Liu, Pengda (Frontiers in Immunology, 2022)
The innate immune response is the first-line host defense against pathogens. Cytosolic nucleic acids, including both DNA and RNA, represent a special type of danger signal to initiate an innate immune response. Activation of cytosolic nucleic acid sensors is tightly controlled in order to achieve the high sensitivity needed to combat infection while simultaneously preventing false activation that leads to pathologic inflammatory diseases. In this review, we focus on post-translational modifications of key cytosolic nucleic acid sensors that can reversibly or irreversibly control these sensor functions. We will describe phosphorylation, ubiquitination, SUMOylation, neddylation, acetylation, methylation, succinylation, glutamylation, amidation, palmitoylation, and oxidation modifications events (including modified residues, modifying enzymes, and modification function). Together, these post-translational regulatory modifications on key cytosolic DNA/RNA sensing pathway members reveal a complicated yet elegantly controlled multilayer regulator network to govern innate immune activation.